Analysis of Solution Space-Dependent Performance of Simulated Annealing: The Case of the Multi-level Capacitated Lot Sizing Problem - Barbarasoğlu, G; Özdamar, Linet (PERGAMON-ELSEVIER SCIENCE LTD, THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND, 2000)
This study describes an analysis of different neighbourhood transition schemes and their effects; on the performance of a general purpose simulated annealing (SA) procedure in solving the dynamic multi-level capacitated lot sizing problem (MLCLSP) with general product structures. The proposed neighbourhood transition schemes are based on relaxing different types of constraints, each of which defines a different solution space. The experiments assess the influence of expanding the search space which includes infeasibilities arising from the elimination of different model restrictions. The results indicate that the performance of SA is highly dependent on the definition and the tightness of the search space. Furthermore, the increase in the number of search moves carried out by SA is shown to significantly improve the results with linearly increasing computational times.
Keywords: simulated annealing; neighbourhood transition schemes; capacitated lot sizing with setup times; ısıl işlem; mahalle geçiş şemaları; setup süreleri ile kapasitan lot boyutlandırma